Contemporary Issues in Higher Education: Diversity, Inclusion, Management and Governance - Makuve , Nyasha (African Journal of Education and Practice, 2024)
Purpose: Teachers, students, and the administration of higher education institutions face a variety of opportunities and challenges as a result of diversity and inclusion. This study looks at diversity and inclusion as a current concern in postsecondary education from the perspectives of instructors, students, and institutional administration. It aims to offer suggestions for dealing with these problems in universities. Higher education institutions are independent and not subject to government oversight in the same manner as public sector organizations, despite receiving significant public funding. The governance, management, and autonomous status of higher education institutions are other topics covered in this work. Methodology: This review draws from inclusion theory which has transformed the view on diversity management from preventing discrimination, which suits the moral view on equality as procedural or individual justice, to ensuring inclusion, which fits the moral view on equality as recognition of diversity. The information is based on literature from various sources. Findings: This study highlights that diversity and inclusion creates a better workplace for everyone while creating an inclusive learning environment. Good governance assures the quality of decision-making hence promotes effective delivery of educational services in a higher learning institution. Unique Contribution to Theory, Practice and Policy: This review article discusses various initiatives, strategies and challenges on diversity and inclusion in higher education as a contemporary issue. The paper also discusses the differences in management and governance as applied in higher education.